PKM Pada Remaja sebagai Agen Pengembangan Masyarakat Pedesaan di Kelurahan Paccinongang Kabupaten Gowa - Hanafie, Nurharsya Khaer; Ahmad, M.Ridwan Said; Amirullah, Amirullah (Humanis, 2021)
This PKM is expected to be able to inform about the importance and strategic position of youth in the framework of national / regional development both historically and prospectively, provide an understanding of youth about their potential so that it can be actualized in the implementation of development and provide an understanding of the importance of increasing the ability and knowledge and skills of youth in welcoming the future. The output of the PKM is the increased confidence of the younger generation as development agents in their area; increasing the understanding of village officials and the community about the awareness that they carry out community tasks and guidance for future generations; There are several dominant supporting factors that are closely related to the development and development of youth in order to be said to be in harmony, namely the level of education that is owned and active in youth organizations. The final activity of this service was carrying out advocacy at the Paccinongang Village Headquarters, with 33 participants. Furthermore, this activity lasted for 1 day, Saturday. This activity is carried out one day which starts at 08.00- 14.00. This activity is focused on two main materials in relation to the influence of globalization and the role of adolescents as agents of community development. Provision of material is done in two ways, namely the first method using the lecture method and the second method using the question and answer method and discussion.AbstractÂ This PKM is expected to be able to inform about the importance and strategic position of youth in the framework of national / regional development both historically and prospectively, provide an understanding of youth about their potential so that it can be actualized in the implementation of development and provide an understanding of the importance of increasing the ability and knowledge and skills of youth in welcoming the future.The output of the PKM is the increased confidence of the younger generation as development agents in their area; increasing the understanding of village officials and the community about the awareness that they carry out community tasks and guidance for future generations; There are several dominant supporting factors that are closely related to the development and development of youth in order to be said to be in harmony, namely the level of education that is owned and active in youth organizations. The final activity of this service was carrying out advocacy at the Paccinongang Village Headquarters, with 33 participants. Furthermore, this activity lasted for 1 day, Saturday. This activity is carried out one day which starts at 08.00-14.00. This activity is focused on two main materials in relation to the influence of globalization and the role of adolescents as agents of community development. Provision of material is done in two ways, namely the first method using the lecture method and the second method using the question and answer method and discussion